Letter: how frequently does COVID‐19 mimic an IBD flare when community transmission of SARS‐CoV‐2 is active?. Issue 5 (10th February 2021) - O'Morain, Neil; Coe, Carolann; Mallon, Patrick; Twomey, Patrick; De Gascun, Cillian F.; Doherty, Glen A.
Abstract : LINKED CONTENT This article is linked to Taxonera et al paper. To view this article, visit https://doi.org/10.1111/apt.15804